Four cycles of docetaxel plus cisplatin as neoadjuvant chemotherapy followed by concurrent chemoradiotherapy in stage N2-3 nasopharyngeal carcinoma: phase 3 multicentre randomised controlled trial - Xie, Wei-Hao; Xiao, Wei-Wei; Chang, Hui; Xu, Ming-Jun; Hu, Yong-Hong; Zhou, Tong-Chong; Zhong, Qiong; Chen, Chun-Yan; Lu, Li-Xia; Wang, Qiao-Xuan; Zhu, Yu-Jia; Yang, Jing; et al. (BMJ (Online), 2025)
AbstractObjectiveTo compare the effects of four cycles of docetaxel with cisplatin as a neoadjuvant chemotherapy followed by concurrent chemoradiotherapy with concurrent chemoradiotherapy alone by assessing reductions in distant metastasis and improvements in survival in patients with stage N2-3nasopharyngeal carcinoma.DesignPhase 3, multicentre, randomised controlled trial.SettingSix sites in China from 23 February 2016 to 18 February 2019.Participants186 participants aged ≤70 years with a diagnosis of untreated stage T1-4N2-3M0 nasopharyngeal carcinoma.InterventionParticipants were prospectively enrolled and randomly allocated to either the neoadjuvant chemotherapy plus concurrent chemoradiotherapy group (four cycles of neoadjuvant chemotherapy (docetaxel 75 mg/m2 on day 1 and cisplatin 37.5 mg/m2 on days 2-3, every 3 weeks) followed by concurrent chemoradiotherapy (intensity modulated radiotherapy plus weekly cisplatin 40 mg/m2) or the concurrent chemoradiotherapy only group, in a 1:1 ratio.Main outcome measuresFive year distant metastasis-free survival and overall survival were analysed using the intention-to-treat approach.Results93 participants were assigned to each of the neoadjuvant chemotherapy plus concurrent chemoradiotherapy and concurrent chemoradiotherapy only groups. After a median follow-up time of 76.9 (interquartile range 65.4-85.9) months, the neoadjuvant chemotherapy plus concurrent chemoradiotherapy group had superior five year distant metastasis-free survival (91.3% (95% confidence interval (CI) 85.4% to 97.2%) versus 78.2% (69.8% to 86.6%); hazard ratio 0.41 (95% CI 0.19 to 0.87); P=0.02) and five year overall survival (90.3% (84.2% to 96.4%) versus 82.6% (75.0% to 90.2%); hazard ratio 0.38 (0.18 to 0.82); P=0.01). Grade 3/4 acute toxicities were observed in 60 (65%) and 46 (51%) patients in the neoadjuvant chemotherapy plus concurrent chemoradiotherapy and concurrent chemoradiotherapy only groups, respectively (P=0.05). The higher acute toxicity observed in the neoadjuvant chemotherapy plus concurrent chemoradiotherapy group was primarily due to grade 3/4 neutropenia (43 (47%) v 10 (11%); P<0.001). No significant difference in any late toxicity was observed between the two groups, and participants in the neoadjuvant chemotherapy plus concurrent chemoradiotherapy group tended to have a better quality of life five years after enrolment.ConclusionsFour cycles of docetaxel plus cisplatin neoadjuvant chemotherapy with concurrent chemoradiotherapy can effectively reduce distant metastasis and improve survival for patients with stage N2-3 nasopharyngeal carcinoma with manageable toxicities.Trial registrationClinicalTrials.gov NCT02512315.